PENINGKATAN MUTU PENDIDIKAN MENURUT HASSAN HUSSEIN AL-BAYLAWI - Nuril Iliana Mingka (UNZAH Genggong, 2022)
The quality of education is the school's ability to manage operationally and efficiently the components related to the school so as to produce added value to these components according to applicable norms or standards. To improve the quality of education, it can be done in a comprehensive way which includes all elements in education in order to achieve good expectations, starting with building most of the school buildings, conducting technology socialization and finally conducting training for each teacher or educator. In this study the authors used a type of library research. The data sources used by researchers were in the form of books, journals and other documents that were useful as supporting data in this study with a qualitative approach. The results of this study criticize education according to Husein Albalawi. the concept of Hassan Hussein al-baylawi places more emphasis on teacher quality, the better the quality of the teacher, the better the quality of education will be guaranteed. It is undeniable that improving the quality of teacher education is one of the indicators that determines whether the quality of education is good or not, but in reality good teacher quality cannot be a guarantee for improving the quality of education, because it will not work if teachers cannot meet the needs of teachers. students or do not understand the situation of students. To improve the quality of education is not only seen from the three pillars that Hassa Hussein al-Baylawi said, but in improving the quality of education it must be seen from many sides, namely the quality components. This section is a supporter and a prerequisite for having quality, some of the components include quality-oriented leadership, education and training, support structures, communication, rewards and recognition, and the last is measurement. Keywords: education, quality improvement, teacher